Analisa Perencanaan Penangkal Petir Pada Gedung Kampus Bima Sakti IST Akprind Yogyakarta - Syafriyuddin; M Suyanto; Subandi Subandi; M Erfan Efendi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2019)
A natural phenomenon such as Lightning that occurs when the upper atmosphere is unstable due to the convergence of a column of warm vertical air, with a cooler mass of air above which is heated by the sun, this rising air current carries water vapor which, while filling cold air , usually condenses, causing convective storm activity, this lightning can be one of the natural causes of injury to humans or damage to electrical equipment. In planning the installation of lightning rods in the Bima Sakti IST Akprind Yogyakarta campus building using KURN R80 type with electrostatic lightning rods. For the cable carrying from the end to the control tub using the NYA cable while for grounding cable using BC cable that is connected to the ground root with a type of ground root stem which has a length of 1.5 m and a diameter of 1.5 cm. From the results of the soil resistance test, get a calculated result of 4,95 Ω, and calculated using a measuring instrument to get a result of 1.16 Ω. With the nonconventional space method in IST Akprind Yogyakarta campus building 3, the total building height up to the 27 meter final is obtained 130.4 m strike distance and 52.46 ° protection angle with a 79.45 m protection radius.